Divje babe I - an attempt to apply statistical analysis to the mass animal remains in the palaeolithic archaeology. IV. Isolated teeth of cave bear - Turk, Ivan; Dirjec, Janez; Debeljak, Irena; Huber, Duro (Arheološki vestnik, 1992)
The contribution gives a presentation of all isolated teeth of the cave bear (Ursus spelaeus) originating from the Divje babe I cave, an Upper Pleistocene Palaeolithic site in Slovenia. All the as yet unpublished archaeological remains belong to the Mousterian (a number of layers) and to the Aurignacian (one layer). Permanent teeth were studied in terms of taphonomic, palaeoeconomic and palaeoecological analyses. In the course of the taphonomic analysis, results of different methods of fieldwork and deskwork were compared. The palaeoeconomic analysis discussed the question of the cave bear being hunted or not. The palaeoecological analysis studied the complex interrelationship between age and sex structures of the fossil populations of the cave bear through the passage of time. The interpretation of the results of the analysis drew on cthological studies and individual ecofacts obtained by means of pollen and sedimentological-stratigraphic analyses. For some of the clearly evident interrelated changes in age and sex structures, an interpretation alternative to the Bergmann rule has been proposed. This alternative interpretation is mostly based on how we answer the question, who made use of the cave-den at a specific period of time, i.e. whether the cave was exclusively used by dominant males or exclusively by cubs and females with cubs.